2008
DOI: 10.1200/jco.2007.13.6424
|View full text |Cite|
|
Sign up to set email alerts
|

Estrogen- and Progesterone-Receptor Status in ECOG 2197: Comparison of Immunohistochemistry by Local and Central Laboratories and Quantitative Reverse Transcription Polymerase Chain Reaction by Central Laboratory

Abstract: There is a high degree of concordance among local IHC, central IHC, and central RT-PCR by the proprietary gene assay for ER and PR status. Although ER expression is marginally associated with relapse in ER-positive patients treated with chemohormonal therapy, recurrence score is a highly significant predictor of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
145
4
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(174 citation statements)
references
References 26 publications
19
145
4
6
Order By: Relevance
“…When individual datasets were used as ''training'' set similar accuracies were obtained in the resulting validation sets (Supplementary Figure 11). Our observed accuracy of ER (91.6%, Table 2) was higher than that between local and central IHC in a recent study from the ECOG 2,197 trial (90%) [51]. In the same study the PgR sensitivity and specificity between local and central IHC were 80.7 and 88.6%, respectively.…”
Section: Discussioncontrasting
confidence: 57%
“…When individual datasets were used as ''training'' set similar accuracies were obtained in the resulting validation sets (Supplementary Figure 11). Our observed accuracy of ER (91.6%, Table 2) was higher than that between local and central IHC in a recent study from the ECOG 2,197 trial (90%) [51]. In the same study the PgR sensitivity and specificity between local and central IHC were 80.7 and 88.6%, respectively.…”
Section: Discussioncontrasting
confidence: 57%
“…However, both fractionated ER and PR in the present study were shown to display a bimodal distribution, with substantial proportions at F scores of 0 (ER: 30.8%; PR: 29.8%) and 5 (ER: 46.6%; PR: 39.4%) ( Table 1). The distribution was consistent with several previous studies of ER and PR expression measured by immunohistochemical assay (Collins et al, 2005;Nadji et al, 2005;Stendahl et al, 2006;Badve et al, 2008;Viale et al, 2008). Despite the bimodal distribution of ER and PR expression, the present study clearly demonstrates that fractionated ER and PR scores predict a patient's prognosis more accurately than a dichotomized assessment.…”
Section: Discussionsupporting
confidence: 81%
“…However, in regards to PR, immunohistochemistry PR-negative cases that were RT-PCR positive were less common than immunohistochemistry PR-positive cases that were RT-PCR negative (similar to our study). The reasons for the difference between Badve et al study and our study include immunohistochemistry analysis on very small samples (ie tissue microarray), and possibly using less optimally fixed tissue and less sensitive antibodies by Badve et al 23 In our study, initial immunohistochemistry was performed on core biopsies, whereas resection specimens were used for the RT-PCR assay. Studies suggest high concordance between qualitative ER expression in core biopsies versus resection specimens.…”
Section: Discussionmentioning
confidence: 88%